Determinants of Accounting Information Use among Micro, Small, and Medium Enterprises in Bengkalis Regency - Siti Asiam (JURNAL ECONOMINA, 2026)
The use of accounting information plays an important role in supporting decision-making and improving the performance of Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs still experience limitations in utilizing accounting information effectively. This study aims to examine the effects of owner education, accounting knowledge, accounting training, and information technology utilization on the use of accounting information among MSMEs in Bengkalis Regency. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 140 MSME owners and analyzed using multiple linear regression with SPSS 29. The findings reveal that accounting knowledge has a positive and significant effect on the use of accounting information, whereas owner education, accounting training, and information technology utilization do not have significant effects. Simultaneously, the four independent variables significantly influence the use of accounting information (F = 10.390; p < 0.001). The coefficient of determination (R2 = 0.235) indicates that the model explains 23.5% of the variation in accounting information use, while the remaining 76.5% is explained by other factors outside the model. These findings contribute to Human Capital Theory by demonstrating that specific competencies, particularly accounting knowledge, play a more important role than formal education, accounting training, or information technology utilization in encouraging MSMEs to use accounting information. Practically, the study suggests that policymakers and relevant institutions should prioritize competency-based accounting education and continuous mentoring programs to improve accounting information utilization amongMSMEs.